New insights into the disulfide bond formation enzymes in epidithiodiketopiperazine alkaloids - Liu, Huan; Fan, Jie; Zhang, Peng; Hu, Youcai; Liu, Xingzhong; Li, Shu-Ming; Yin, Wen-Bing (Chemical science (Cambridge), 2021)
Epidithiodiketopiperazines (ETPs) are a group of bioactive fungal natural products and structurally feature unique transannular disulfide bridges between α, α or α, β carbons. However, no enzyme has yet been demonstrated to catalyse α, β-disulfide bond formation in these molecules. Through genome mining and gene deletion approaches in Trichoderma hypoxylon , we identified a putative biosynthetic gene cluster of pretrichodermamide A ( 1 ), which requires a FAD-dependent oxidoreductase, TdaR, for the irregular α, β-disulfide formation in 1 biosynthesis. In vitro assays of TdaR, together with AclT involved in aspirochlorine and GliT involved in gliotoxin biosynthesis, proved that all three enzymes catalyse not only the conversion of red-pretrichodermamide A ( 4 ) to α, β-disulfide-containing 1 but also that of red-gliotoxin ( 5 ) to α, α-disulfide-containing gliotoxin ( 6 ). These results provide new insights into the thiol-disulfide oxidases responsible for the disulfide bond formation in natural products with significant substrate and catalytic promiscuities. A FAD-dependent oxidoreductase TdaR was responsible for α, β-disulfide formation in the biosynthesis of pretrichodermamide A. TdaR, together with its homologs AclT and GliT, catalysed not only α, α- but also α, β-disulfide formation in fungi.